2020
DOI: 10.1038/s41467-020-16515-y
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomic analysis identifies the conversion of zebrafish Etv2-deficient vascular progenitors into skeletal muscle

Abstract: Cell fate decisions involved in vascular and hematopoietic embryonic development are still poorly understood. An ETS transcription factor Etv2 functions as an evolutionarily conserved master regulator of vasculogenesis. Here we report a single-cell transcriptomic analysis of hematovascular development in wild-type and etv2 mutant zebrafish embryos. Distinct transcriptional signatures of different types of hematopoietic and vascular progenitors are identified using an etv2 ci32Gt gene trap line, in which the Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 69 publications
(96 reference statements)
9
37
0
Order By: Relevance
“…In the past 12 months, scRNAseq-based studies also found further evidence of endothelial plasticity during development, 65–67 and revealed novel mechanisms of vascular remodelling in hypertension 68 and ageing. 69 , 70 Indeed, cell plasticity provides new opportunities for therapeutic targeting as shown this year by Artiach et al 71 who found that omega-3 polyunsaturated fatty acids can protect against aortic valve stenosis by activating a pathway involved in smooth muscle cell phenotypic switching, 72 and the elucidation of oligomeric S100A4-TLR4-NFκB pathway driving VSMC phenotypic transition in atherosclerosis.…”
Section: Single Cell Omics and Cell Plasticitymentioning
confidence: 92%
“…In the past 12 months, scRNAseq-based studies also found further evidence of endothelial plasticity during development, 65–67 and revealed novel mechanisms of vascular remodelling in hypertension 68 and ageing. 69 , 70 Indeed, cell plasticity provides new opportunities for therapeutic targeting as shown this year by Artiach et al 71 who found that omega-3 polyunsaturated fatty acids can protect against aortic valve stenosis by activating a pathway involved in smooth muscle cell phenotypic switching, 72 and the elucidation of oligomeric S100A4-TLR4-NFκB pathway driving VSMC phenotypic transition in atherosclerosis.…”
Section: Single Cell Omics and Cell Plasticitymentioning
confidence: 92%
“…Via in situ hybridization, lineage tracing and confocal microscopy, we successfully traced the origin of the ectopic β-cells to the mesodermal lineage. A recent study has reported the conversion of Etv2-deficient vascular progenitors into skeletal muscle cells, and highlighted the plasticity of mesodermal cell fate determination within the same germ layer (Chestnut et al, 2020). Our data demonstrated the plasticity of β-cell differentiation across the committed germ layers in vivo , i.e., switching from a mesodermal to an endodermal fate in a regenerative setting, while gastrulation and cell fate commitment in the germ layers are considered to be irreversible in development.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, when BMP signal inhibition is relieved, PAA progenitors are capable of reappearing in the pharyngeal mesoderm and develop into growing sprouts. Previous studies have revealed that npas4l functions upstream of etv2 , and etv2 -deficient vascular progenitors can acquire a skeletal muscle fate, whereas overexpression of etv2 induces vascular gene expression and converts skeletal muscle cells into functional endothelial cells ( Chestnut et al, 2020 ; Reischauer et al, 2016 ; Veldman et al, 2013 ; Yan et al, 2019a ). Therefore, when BMP signal is reactivated after the washout of BMP inhibitors, the expression of npas4l and its downstream gene etv2 might be reinduced in the muscle progenitors located in the presumptive PAA clusters and then transdifferentiated into endothelial cells.…”
Section: Discussionmentioning
confidence: 99%